2007
DOI: 10.1682/jrrd.2007.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Anodal and cathodal pulsed electrical stimulation on skin wound healing in guinea pigs

Abstract: Abstract-We investigated the effects of anodal and cathodal electrical stimulation on wound healing. In a randomized controlled trial, we divided 42 male albino guinea pigs into two control (C1 and C2) and four experimental (E1-E4) groups. A 3 cm linear incision was made at the dorsal skin of all guinea pigs. A unidirectional pulse current of 300 to 600 microamperes, 80 pps, and 0.3 ms pulse duration was administered for 1 hour a day. In groups E1 and E3 (anodal), a positive polarity was applied for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…In the motor ES group, we applied monophasic pulsed current with an intensity enough to elicit a visible minimum contraction (about 2.5-3.0 mA), pulse duration 300 s, frequency 100 Hz, for 1 h/day, every other day, for 3 or 7 days. These ES parameters have been used in many other studies [15,[17][18][19]. The ES device used in this study was the BTL-5000 series (BTL Industries Ltd; Hertfordshire, United Kingdom).…”
Section: Wounding and Treatment Protocolmentioning
confidence: 99%
“…In the motor ES group, we applied monophasic pulsed current with an intensity enough to elicit a visible minimum contraction (about 2.5-3.0 mA), pulse duration 300 s, frequency 100 Hz, for 1 h/day, every other day, for 3 or 7 days. These ES parameters have been used in many other studies [15,[17][18][19]. The ES device used in this study was the BTL-5000 series (BTL Industries Ltd; Hertfordshire, United Kingdom).…”
Section: Wounding and Treatment Protocolmentioning
confidence: 99%
“…There are controversial results from previous studies regarding the effects of ES on the biomechanical properties of healed wounds [30][31]34,[36][37][45][46][47][48]. Although a comparison of the biomechanical properties showed no statistically significant differences between the normalized ultimate strength, stiffness, and strain in the groups, these biomechanical properties tended to be higher in the motor ES group.…”
Section: Groupmentioning
confidence: 76%
“…ES has beneficial effects on the wound-healing process [9][10][11][12][13][14][15][35][36][37], but the mechanism of these effects remains unclear. Angiogenesis factors play an important role in various phases of wound healing [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the antibacterial effect of negative-polarity stimulation [16][17][18] and the relationship between faster wound epithelialization and positive-polarity stimulation [19]. After observing the different physiopathologic effects caused by positive-and negative-polarity stimulation, a study was conducted in which the stimulus polarity was alternated along the treatment [20]. The authors reported that alternated-polarity stimuli, which are similar to the currents produced by the human body in response to a skin wound, accelerated the wound healing process [21].…”
Section: Discussionmentioning
confidence: 99%